Air quality and health impact of 2019–20 Black Summer megafires and COVID-19 lockdown in Melbourne and Sydney, Australia. (1st April 2021) - Ryan, Robert G.; Silver, Jeremy D.; Schofield, Robyn
Abstract: Poor air quality is an emerging problem in Australia primarily due to ozone pollution events and lengthening and more severe wildfire seasons. A significant deterioration in air quality was experienced in Australia's most populous cities, Melbourne and Sydney, as a result of fires during the so-called Black Summer which ran from November 2019 through to February 2020. Following this period, social, mobility and economic restrictions to curb the spread of the COVID-19 pandemic were implemented in Australia. We quantify the air quality impact of these contrasting periods in the south-eastern states of Victoria and New South Wales (NSW) using a meteorological normalisation approach. A Random Forest (RF) machine learning algorithm was used to compute baseline time series' of nitrogen dioxide (NO2 ), ozone (O3 ), carbon monoxide CO and particulate matter with diameter < 2 . 5  μ m (PM2 . 5 ), based on a 19 year, detrended training dataset. Across Victorian sites, large increases in CO (188%), PM2 . 5 (322%) and ozone (22%) were observed over the RF prediction in January 2020. In NSW, smaller pollutant increases above the RF prediction were seen (CO 58%, PM2 . 5 80%, ozone 19%). This can be partly explained by the RF predictions being high compared to the mean of previous months, due to high temperatures and strong wind speeds, highlighting the importance of meteorological normalisation in attributing pollution changes to specific events. From the daily observation-RF prediction differences we estimated 249.8 (95% CI: 156.6–343.) excess deaths and 3490.0 (95% CI 1325.9–5653.5) additional hospitalisations were likely as a result of PM2 . 5 and O3 exposure in Victoria and NSW. During April 2019, when COVID-19 restrictions were in place, on average NO2 decreased by 21.5 and 8% in Victoria and NSW respectively. O3 and PM2 . 5 remained effectively unchanged in Victoria on average but increased by 20 and 24% in NSW respectively, supporting the suggestion that community mobility reduced more in Victoria than NSW. Overall the air quality change during the COVID-19 lockdown had a negligible impact on the calculated health outcomes. Graphical abstract: Image 1 Highlights: Air pollution in Australia was modelled using meteorological normalisation. Accounting for meteorology is necessary for attributing air quality impacts. Air quality improvement during COVID-19 lockdown highly regionally dependent. PM2.5 and O3 from Black Summer smoke likely caused 187 excess deaths.